Assessment and Classification of Service Learning: A Case Study of CS/EE Students - Han-Ying Kao; Yu-Tseng Wang; Chia-Hui Huang; Pao-Lien Lai; Jen-Yeu Chen (The Scientific World Journal)
This study investigates the undergraduate students in computer science/electric engineering (CS/EE) in Taiwan to measure their perceived benefits from the experiences in service learning coursework. In addition, the confidence of their professional disciplines and its correlation with service learning experiences are examined. The results show that students take positive attitudes toward service learning and their perceived benefits from service learning are correlated with their confidence in professional disciplines. Furthermore, this study designs the knowledge model by Bayesian network (BN) classifiers and term frequency-inverse document frequency (TFIDF) for counseling students on the optimal choice of service learning.